Adaptation and validation of the Charlson Index for Read/OXMIS coded databases - Khan, N; Perera, R; Harper, S; Rose, P (BioMed Central, 2010)
Background: The Charlson comorbidity index is widely used in ICD-9 administrative data, however, there is no translation for Read/OXMIS coded data despite increasing use of the General Practice Research Database (GPRD). Our main objective was to translate the Charlson index for use with Read/OXMIS coded data such as the GPRD and test its association with mortality. We also aimed to provide a version of the comorbidity index for other researchers using similar datasets. Methods: Two clinicians translated the Charlson index into Read/OXMIS codes. We tested the association between comorbidity score and increased mortality in 146 441 patients from the GPRD using proportional hazards models. Results: This Read/OXMIS translation of the Charlson index contains 3156 codes. Our validation showed a strong positive association between Charlson score and age. Cox proportional models show a positive increasing association with mortality and Charlson score. The discrimination of the logistic regression model for mortality was good (AUC = 0.853). Conclusion: We have translated a commonly used comorbidity index into Read/OXMIS for use in UK primary care databases. The translated index showed a good discrimination in our study population. This is the first study to develop a co-morbidity index for use with the Read/OXMIS coding system and the GPRD. A copy of the co-morbidity index is provided for other researchers using similar databases.